Deuteration of C60 on a highly oriented pyrolytic graphite surface. Issue Volume 15:Issue S350(2019) (April 2019) - Pantazidis, G.; Scheffler, M.; Simonsen, F. D. S.; Cassidy, A.; Jensen, P. A.; Hornekær, L.; Thrower, J. D.
Abstract: Reactions on carbonaceous surfaces play an important role in processes such as H2 formation in the interstellar medium. We have investigated the adsorption of C2 molecules on a highly oriented pyrolytic graphite (HOPG) surface and then exposed them to a beam of deuterium atoms in order to investigate the formation of deuterated fullerenes. Scanning tunneling microscopy (STM) was used to probe the adsorbed molecules and their deuteration. Deuteration of C2 films results in increased thermal stability of the film, relative to films of pristine C2, along with an evolution towards higher deuterated species. The STM data provide confirmatory evidence for the formation of deuterated fullerene species.